SCOPE FOR THE IMPLEMENTATION OF UNIFORM CIVIL CODE IN CONTEMPORARY INDIA: A SUGGESTION - MEGHA OJHA (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Indian Constitution provides provision for the implementation of Uniform Civil Code (UCC) in India. Article 44 of the Indian Constitution gives direction to the State to implement it, but the UCC could not be implemented in India due to various conflicts in personal laws. The Supreme Court of India in various cases has given direction to the Government to implement UCC but due to lack of political determination, it could not be achieved. Significantly, the requirement of UCC had been raised repeatedly before independence too, but nothing could be achieved even after 73 years of independence. Thus, the question is that whether India is ready to implement UCC to fulfil requirement of modern world and its citizens. Juristically, socially and probably politically it is well understood that UCC is the need of the hour; and therefore, it should be implementedin India, but at this point uncertaintyis that, whether it has to be implemented in India step by step by increasing awareness about it or it should be implemented in India forcefully. In this research paper, the researcher will be primarily distillate on various dimensions of Uniform Civil Code. The research paper shall attempt to establish that why Indians can expect now for effective implementation of UCC by the Indian Government.